Controlled release of poly(vinyl sulfonate) scale inhibitor to extend reservoir treatment lifetime. Issue 12 (30th October 2018) - Veisi, Masoumeh; Johnson, Stephen; Shafer‐Peltier, Karen; Liang, Jenn‐Tai; Berkland, Cory; Chen, Ming; Barati, Reza
ABSTRACT: Precipitate scale formation is a major issue for the oil industry, plugging equipment, and reservoirs and resulting in increased operational costs. Poly(vinyl sulfonate) (PVS) is often used as a scale inhibitor to prevent the formation of barium sulfate scale. However, PVS effectiveness is limited by its short lifetime in reservoir. In this article, PVS has been entrapped in polyelectrolyte complex nanoparticles (PECNPs), altering its charge and thus enabling improved adsorption on the rock surface. As the ionic strength of the surrounding brine increases, the PVS is then released from the PECNPs, making it available to inhibit scale formation gradually. Positively charged PECNPs were made using a combination of poly(ethyleneimine) (PEI) and PVS. After NPs optimization, static adsorption tests were performed, which confirm the nanoparticles' rapid and strong adsorption. An increase in the ionic strength of the displacing fluid was used to decompose the PECNPs structure and release the PVS into solution. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47225. Abstract :